2‐Hydroxyisocaproic acid is bactericidal in human dental root canals ex vivo. (15th April 2016) - Sakko, M.; Tjäderhane, L.; Sorsa, T.; Hietala, P.; Rautemaa, R.
Abstract: Aim: To compare the activity of 2‐hydroxyisocaproic acid (HICA), calcium hydroxide (Ca(OH)2 ) and chlorhexidine digluconate (CHG) against Enterococcus faecalis T‐75359 (root canal isolate) in the root canals of extracted human teeth. Methodology: Bacterial suspensions (10 8  cfu mL −1 ) were incubated in root canals with 0.9 mm diameter root blocks ( n  = 73) for 21 days. Bacterial penetration into dentine was analysed by the Brown and Brenn method ( n  = 5). Canals ( n  = 17/group) were medicated with 40% of HICA paste, 40% of Ca(OH)2 paste, 2% of CHG solution or 0.9% of saline solution for 7 days. Samples taken from the inner (first 0.1 mm) and deeper (second 0.1 mm) dentine, and residual roots were cultured in broth for 24 h. Bacterial growth was detected by spectrophotometry (optical density, OD) and confirmed by culture on agar. The OD data were analysed with Kruskal–Wallis and Friedman with Wilcoxon signed‐rank test between and within groups, respectively, and agar culture data with Pearson chi‐square with Mann–Whitney and Cochran with McNemar tests, respectively ( P  < 0.05). Results: Bacterial invasion into dentine tubules was confirmed. In deeper dentine, HICA inhibited >90% of bacterial growth in comparison with saline. No bacterial growth was observed in 82–100% of inner and deeper dentine samples. CHG prevented the growth in 88%, Ca(OH)2 in 59–76% and saline in 65–71%, respectively. HICA was significantly more active than Ca(OH)2 ( P  = 0.008) in the residual roots. The viability testing on agar showed essentially the same result. Conclusion: HICA paste exerted superior activity against E. faecalis and could have potential for root canal medication.